The mock modular data of a family of superalgebras - Alfes, Claudia; Creutzig, Thomas (Proceedings of the American Mathematical Society, 2014)
The modular properties of characters of representations of a family of W-superalgebras extending gl(1|1) are considered. Modules fall into two classes, the generic type and the non-generic one. Characters of non-generic modules are expressed in terms of higher-level Appell-Lerch sums. We compute the modular transformations of characters and interpret the Mordell integral as an integral over characters of generic representations. The C-span of a finite number of non-generic characters together with an uncountable set of characters of the generic type combine into a representation of SL(2;Z). The modular transformations are then used to define a product on the space of characters. The fusion rules of the extended algebras are partially inherited from the known fusion rules for modules of gl(1|1). Moreover, the product obtained from the modular transformations coincides with the product of the Grothendieck ring of characters if and only if the fusion multiplicities are at most one.
CRIS-Team Scopus Importer:2024-06-24